+0  
 
0
63
2
avatar

Solve \(9^x - 2 \cdot 3^x - 63 = 0\)

 Jun 30, 2020
 #1
avatar+21953 
0

Solve:         9x - 2·3x - 63  =  0

Rewrite:  (32)x - 2·3x - 63  =  0

                  32x - 2·3x - 63  =  0

Factor:      (3x - 9)(3x + 7)  =  0

 

Either:     3x  =  9     --->     x  =  2

or:           3x  =  -7    --->    (no real solution)    

 Jun 30, 2020
 #2
avatar+1130 
+1

we get (9^x)-2*(3^x)=63 by adding 63 to both sides and then we use elimination.Finally we get x=2 so the only way for x is 2

 Jun 30, 2020
edited by jimkey17  Jun 30, 2020

28 Online Users

avatar